Setting the geological scene for the origin of life and continuing open questions about its emergence - Westall, Frances; Brack, André; Fairén, Alberto G.; Schulte, Mitchell D. (Frontiers in Astronomy and Space Sciences, 2023)
The origin of life is one of the most fundamental questions of humanity. It has been and is still being addressed by a wide range of researchers from different fields, with different approaches and ideas as to how it came about. What is still incomplete is constrained information about the environment and the conditions reigning on the Hadean Earth, particularly on the inorganic ingredients available, and the stability and longevity of the various environments suggested as locations for the emergence of life, as well as on the kinetics and rates of the prebiotic steps leading to life. This contribution reviews our current understanding of the geological scene in which life originated on Earth, zooming in specifically on details regarding the environments and timescales available for prebiotic reactions, with the aim of providing experimenters with more specific constraints. Having set the scene, we evoke the still open questions about the origin of life: did life start organically or in mineralogical form? If organically, what was the origin of the organic constituents of life? What came first, metabolism or replication? What was the time-scale for the emergence of life? We conclude that the way forward for prebiotic chemistry is an approach merging geology and chemistry, i.e., far-from-equilibrium, wet-dry cycling (either subaerial exposure or dehydration through chelation to mineral surfaces) of organic reactions occurring repeatedly and iteratively at mineral surfaces under hydrothermal-like conditions.